If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 63 = 7(x + -9) Reorder the terms: 63 + 5x = 7(x + -9) Reorder the terms: 63 + 5x = 7(-9 + x) 63 + 5x = (-9 * 7 + x * 7) 63 + 5x = (-63 + 7x) Solving 63 + 5x = -63 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 63 + 5x + -7x = -63 + 7x + -7x Combine like terms: 5x + -7x = -2x 63 + -2x = -63 + 7x + -7x Combine like terms: 7x + -7x = 0 63 + -2x = -63 + 0 63 + -2x = -63 Add '-63' to each side of the equation. 63 + -63 + -2x = -63 + -63 Combine like terms: 63 + -63 = 0 0 + -2x = -63 + -63 -2x = -63 + -63 Combine like terms: -63 + -63 = -126 -2x = -126 Divide each side by '-2'. x = 63 Simplifying x = 63
| n-7=13 | | x+2/3= | | x^2-2x=21 | | X^2-4x+5=10 | | -5(3x+7)=-15 | | 7x-9=2x+21 | | 3x-9y-8x+7y= | | x+2= | | x^2+2x=19 | | 6(5z-1)-4(z+6)=3(z+1) | | X^2-10+16=0 | | 4(x+2)-6=2x-7 | | 2x-3=5x+12 | | -3x-9=-2x-7 | | 3(5r+5)-4(r-3)= | | 260+40x= | | 4a+7b= | | 2x-3=3x-6 | | 100-8+677543-3= | | 4x^2-15x+9=-8x+6 | | 3(2x+5)+4(3x+2)=104 | | x^2-12x+6=0 | | 4(-1+2)-6=2x-7 | | 3x+5=-4x-9 | | 27x^2-12=0 | | 2x+54=8x-6 | | 2x+7=4x-15 | | (5x+7)(4x-1)=0 | | 4x=12(x-40) | | 3x^2+1=x^2-1 | | 38-(2x+7)=2(x+3)+x | | 3x+.5=2x+.62 |